The Mardzong manuscripts: codicological and historical studies of an archaeological find in Mustang, Nepal - Helman-Ważny, Agnieszka (Brill's Tibetan studies library, 2021)
"In 2008, an international team of climbers discovered a large collection of Tibetan manuscripts in a cave complex called Mardzong, in Nepal's remote Mustang district. The following year, the entire cache-over five thousand folios from some sixty different works of the Buddhist and Bön religions, some more than seven centuries old-were removed to the safe keeping of a monastery, where they were later examined by experts from different disciplines. This book is the result of their findings. The authors present what they have been able to discover about the content of these manuscripts, their age, the materials with which they were made, the patrons who commissioned them and the scribes and artists who created them. Contributors include: Agnieszka Helman-Ważny, Charles Ramble, Nyima Drandul Gurung, Naljor Tsering, Sarah Skumanov, Emilie Arnaud-Nguyen and Bazhen Zeren"--